Use of a commercial agarose gel for analysis of urinary glycosaminoglycans in mucopolysaccharidoses (Brazilian Journal of Pharmaceutical Sciences, 2016)
Mucopolysaccharidoses (MPS) are a group of inherited metabolic disorders caused by deficiency of enzymes that degrade glycosaminoglycans (GAGs). Urinary excretion of GAGs is a common feature of MPS, and is considered their major biomarker. We aimed to adapt the GAG electrophoresis method to a commercial agarose gel which would be able to separate urinary GAGs in a simpler way with good sensitivity and reproducibility. Urine samples from patients previously diagnosed with MPS I, IV, and VI were used as electrophoretic standards. Samples from patients on enzyme replacement therapy (ERT) were also assessed. Commercial agarose gel electrophoresis was effective, showing proper definition and separation of GAG bands. Detection sensitivity exceeded 0.1 µg and band reproducibility were consistent. GAG bands quantified in urine samples from patients on ERT correlated very strongly (correlation coefficient = 0.98) with total GAG concentrations. This application of gel electrophoresis demonstrates the possibility of monitoring patients with MPS treated with ERT by analyzing separately the GAGs excreted in urine. We suggest this process should be applied to MPS screening as well as to follow-up of patients on treatment.